2007
DOI: 10.1152/ajpregu.00216.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, insulin, and leptin signaling pathways modulate nitric oxide synthesis in glucose-inhibited neurons in the ventromedial hypothalamus

Abstract: Canabal DD, Song Z, Potian JG, Beuve A, McArdle JJ, Routh VH. Glucose, insulin and leptin signaling pathways modulate nitric oxide synthesis in glucose-inhibited neurons in the ventromedial hypothalamus. Am J Physiol Regul Integr Comp Physiol 292: R1418 -R1428, 2007. First published December 24, 2006; doi:10.1152/ajpregu.00216.2006.-Glucose-sensing neurons in the ventromedial hypothalamus (VMH) are involved in the regulation of glucose homeostasis. Glucosesensing neurons alter their action potential frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 44 publications
3
124
0
Order By: Relevance
“…Amylin augmented leptin-stimulated signaling by Ϸ43% in the VMH without improving leptin signaling in the ARC. Within the VMH, enhanced leptin signaling would be expected to positively impact energy regulation because leptin receptors are abundantly expressed on glucose-sensitive VMH neurons, and potent anorexigenic and weight-reducing effects are observed after VMH leptin microinjection (27)(28)(29). Leptin-responsive neurons in the VMH also contain SF-1 (22), a transcription factor whose deficiency induces DIO in mice (30).…”
Section: Discussionmentioning
confidence: 99%
“…Amylin augmented leptin-stimulated signaling by Ϸ43% in the VMH without improving leptin signaling in the ARC. Within the VMH, enhanced leptin signaling would be expected to positively impact energy regulation because leptin receptors are abundantly expressed on glucose-sensitive VMH neurons, and potent anorexigenic and weight-reducing effects are observed after VMH leptin microinjection (27)(28)(29). Leptin-responsive neurons in the VMH also contain SF-1 (22), a transcription factor whose deficiency induces DIO in mice (30).…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, a previously established primary dissociated cortical neuronal culture (Dawson, et al, 1993;Landree, et al, 2004) was maintained in a glucose-free media supplemented with glutamine and B27 and either a physiological concentration of 3 mM glucose (NB-A 3 ), or a non-physiological high concentration of 25 mM glucose (NB-A 25 ). The present study was designed to further develop previous studies that considered the role of media glucose concentrations present during short-term culture (used by DIV4) and/or experimental medias (Wang, et al, 2004;Song, et al, 2005;Morgenthaler, et al, 2006;Abe, et al, 2006;Bak, et al, 2006;Kang, et al, 2006;Canabal, et al, 2007a;Canabal, et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…There are a small number of studies involving neuronal cultures and AMPK modulation with AICAR Chau-Van, et al, 2007;Dasgupta, et al, 2007;Canabal, et al, 2007a;Canabal, et al, 2007b;Mountjoy, et al, 2007), but few which utilize physiological glucose culture conditions Canabal, et al, 2007a;Canabal, et al, 2007b). A previous study using neuroblastoma cell lines cultured in 25 mM glucose demonstrated that basal levels of pAMPK are increased following incubation (16 hour) in media containing glucose below physiological concentrations (0 and 1 mM) relative to those switched to 2.5 mM glucose, and decreased in media containing glucose above physiological levels (5, 10, and 25 mM) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations